Southern engines of global growth: Very long cycles or short spurts? - Meghnad Desai (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This article views the four economies of the South in a long run historical perspective of 1500-2000. It contrasts the history and the initial endowments of the two Northern hemisphere economies China and India which are land scarce and labour abundant with the two Southern hemisphere economies Brazil and South Africa which are land abundant and labour scarce. It argues for different strategies for future growth and discusses impediments which may come in the paths of these four economies in the near future.
Keywords: N1; O11; F54; 330; China; India; Brazil; South Africa; development; history